Do patients with long-term side effects of cancer treatment benefits from general practitioner support? A literature review. - Ngune, Irene; Jiwa, Moyez; McManus, Alexandra; Hughes, Jeff (Utrecht University Library Open Access Journals, 2015)
Background: Alongside specialist cancer clinics, general practitioners have an important role in cancer patients' follow-up care, yet no literature summarises the nature, extent and impact of their involvement. This paper addresses this issue through a review of the literature. Methods: Studies were sourced from six academic databases - AustHealth (n = 202), CINAHL (n = 500), the Cochrane Library (reviews and trials; n = 200), Embase (n = 368), PHCRIS (n = 132) and PubMed/Medline (n = 410). Studies that focused on interventions designed for patients receiving follow-up care and reported cancer care provided by a general practitioner delivered alongside specialist care were reviewed. Results: A total of 19 papers were identified as relevant for this review (3 randomised control trials; 4 cross-sectional, 5 cohort and 3 qualitative studies, and 3 systematic reviews). The reviewed studies indicated that providing general practitioner-led supportive inter- ventions for post-treatment care of cancer patients is feasible and acceptable to patients. General practitioner involvement resulted in improved physical and psychosocial well-being of patients and continuity of care, especially for patients with concomitant health conditions. Conclusion: Involving general practitioners in post-treatment cancer care is beneficial to patients. However, proactive initiatives that encourage and facilitate patients to consult their general practitioner about their needs or symptoms of recurrence should be considered.